Online Shopping Market: Technology to Create New Business Value - Mohan , P.; Reddy, D. Maheswara; Lakshmi, P. (Gyan Management Journal, 2012)
The paper aims at assessing how an e-marketing strategy appears to be a more promising service through Internet channel. Marketing as a business function has witnessed several changes during the last decades. As metrics for success, organizations focus on customer loyalty and customer delight to have a competitive advantage and to stay alive in the market. As such companies have re engineered their business processes by migrating to the cyber space to offer merchandise and services through an electronic channel. Also with the exponential rise of customers opting for on line transaction processing, information systems have changed the way that organizations run businesses in the present day world. A key change involves the adoption of Internet technology such as the Webvertising to carry out business function, resulting in the field of information processing to provide a rich and fertile basis for significant business developments to take place.